A novel approach to determining dynamic nitrogen thresholds for seagrass conservation. Issue 1 (12th August 2018) - Fernandes, Milena B.; van Gils, Jos; Erftemeijer, Paul L. A.; Daly, Rob; Gonzalez, Dennis; Rouse, Karen
Abstract: Seagrass decline is often related to eutrophication, with sudden and drastic losses attributed to tipping points in nutrient loads. The identification of these threshold loads is an important step in the sustainable management of nutrient discharges. In this study, a novel methodological approach is presented to simulate the spatial and temporal dynamics of coastal nitrogen loads and its relationship with seagrass loss. The analysis allows the identification of nitrogen thresholds associated with the loss of Posidonia and Amphibolis spp. in Adelaide, South Australia. The identified thresholds varied between 0.8 and 1.1 t N km −2 over 6 months and explained up to 95% of all seagrass losses in the region. Posidonia spp. was predominantly lost nearshore, indicating a threshold for this species in the higher end of the values reported here. In contrast, Amphibolis spp. were selectively lost further offshore, suggesting a lower threshold for the onset of fragmentation and decline. Nitrogen pressure was concentrated over the wetter months of the year between late autumn and early spring. Pulsed pressure peaking in August likely affected thresholds by reducing resilience in the system. Synthesis and applications . This study derives, for the first time, nitrogen load thresholds for the loss of the seagrasses Posidonia and Amphibolis spp., highlighting the low tolerance of these keystone temperate species to nitrogen pressure. The methodology developed as part of the work provides a tool to inform planning and improved management of nutrient discharges from land to facilitate seagrass conservation. Abstract : This study derives, for the first time, nitrogen load thresholds for the loss of the seagrasses Posidonia and Amphibolis spp., highlighting the low tolerance of these keystone temperate species to nitrogen pressure. The methodology developed as part of the work provides a tool to inform planning and improved management of nutrient discharges from land to facilitate seagrass conservation.